INOVASI MEDIA PEMBELAJARAN BERBASIS ADOBE FLASH CS6 DAN BINSCAN PADA MATERI PERUBAHAN LINGKUNGAN - Gusti, Utari Akhir; Azzahra, Waliyyatu; Widodo, Ari (Borneo Journal of Biology Education (BJBE), 2023)
Learning media has a strategic role in helping teachers in schools. Currently, the majority of teachers use media in the learning process. This has proven to be efficient in increasing students' interest in learning in class. A lot of research has been carried out to develop learning media. However, there are still few who analyze the innovation of original media with digital. So, research was conducted to analyze media-based learning innovationsAdobe flash Ac6 andBinscan on environmental change material. This research is classified as descriptive qualitative. The research aims to provide an overview of learning media innovation. Data collection techniques using observation, interview, and literature study. The results of the research are learning media innovations at the introductory, core and closing stages of learning. The application modified in this research is Adobe Flash. Meanwhile, applications designed to support learning, namelyBinscan. This innovation can be used as consideration for teachers to use in learning at school.